Analisis Perbandingan Kinerja Pengereman ABS Menggunakan Fuzzy Logic Controller dan Bang-Bang Control pada Kondisi Jalan Kering dan Basah - Ilhamdan Prima, Dhovan; Kholid, Ismail; Nasrullah, Hamid (Politeknik Piksi Ganesha Indonesia, 2025)
In this study, The effectiveness of the Anti-Lock Braking System is evaluated by comparing bang-bang control with fuzzy logic control. ABS plays a crucial role in vehicle safety, as it manages braking torque to ensure wheel slip remains at an optimal level, preventing the wheels from locking and maintaining control of the vehicle. A mathematical ABS model was implemented and analyzed using MATLAB/Simulink simulations to examine how both controllers behave. The simulation outcomes highlight that fuzzy logic control performs better than bang-bang control, with advantages such as shorter stopping distances, faster braking responses, and more stable slip control.